When does technological change in agriculture promote deforestation - Angelsen, A.; Kaimowitz, D. (CAB International, 2001)
This chapter attempts to systematically examine some of the main analytical arguments and empirical evidence regarding the impact of technological progress in agriculture on deforestation. Three factors have been highlighted that are important in determining deforestation outcomes: (1) the type of technological change; (2) in which subsectors of agriculture it occurs; (3) in what labour market and product market conditions it occurs. Three conclusions emerge: (1) technological progress in the intensive sector is generally good for forest conservation; (2) labour intensive technological progress will tend to reduce forest clearing; (3) the effect of pure yield increasing and labour-saving technological progress in the extensive sector is sensitive to market assumptions.